Effect of Glutamate Supplementation in Broiler Chicken Feed to The Quality of Carcass - Vebera Maslami; Azhary Noersidiq; Fahrullah Fahrullah; Dwi Kusuma Purnamasari; Yetti Marlida; Mirnawati; Yuliaty Shan Nur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
: Glutamate is an alternative feed additive that is safe and environmentally friendly in improving the quality of broiler chicken carcass. This study aims to determine the effect of glutamate produced by Lactobacilus plantarum MV on the quality of broiler chicken carcass. The aim of this research was to get the optimum doses of glutamate in feed broiler for increasing the quality of carcass. The design used was a Completely Randomized Design (CRD), with 6 treatments and 4 replications. This study used 240 broiler chicken strain MB 202 from PT Charoen Phokphand Indonesia, 1 day old and the treatment started at 7 days of age with 5 weeks of treatment. Each experimental unit consisted of 10 chickens. The Glutamate doses in groups were, A (0.4% commercial glutamate; B (0% glutamate); C (0.2% glutamate); D (0.4% glutamate); E (0.6% glutamate); F (0.8% glutamate). The results indicated that glutamate up to 0.8% had significant effects on carcass quality, consisting of reducing abdominal fat (0,64%) and cholesterol (0,64%), as well as increasing meat protein (73,09%) and cooking losses (26.69%). It can be concluded that 0,8% glutamate in broiler feed was increasing the quality of carcass.